تشكل وتوزع الثمار على السطح المثمر لأشجار تفاح ثم صنفي Goldren delicious,Starking delicious (Latakia University Journal -Biological Sciences Series, 2024)
تشكل وتوزع الثمار على السطح المثمر لأشجار تفاح ثم صنفي Goldren delicious,Starking delicious